Anatomical and Imagistic Aspects of the Aortic Arch in Chinchilla lanigera - Martonos, Cristian; Lăcătuș, Radu; Cocan, Daniel; Stan, Florin; Damian, Aurel; Stroe, Teodor; Dezdrobitu, Cristian; Gudea, Alexandru (Acta Scientiae Veterinariae, 2018)
Background: The investigation on the cardiocirculatory system in chinchilla has become increasingly important due to the use of the species in experimental medicine (toxicology, pathology, parasitology etc.). Even though initially this species was regarded with a strict economic interest, in the last period, chinchillas have become an increasingly-encountered patient in veterinary clinics and hospitals. Another aspect is the use of the species in medical research, as experimental model or in parasitology. The present study tackles a combined anatomical and radiological (angiographical) study to accurately describe the vascular anatomy of the initial part of the aortic arch (Arcus aortae). Materials, Methods & Results: The anatomical distribution of collaterals detached from arcus aorticus (brachiocephalic trunk and subclavian arteries) are highlighted in this paper. To do that, the classical stratigraphic anatomical investigation, followed by the radiological study with the help of the contrast substance injected into the vascular bed were used in combination. Several Chinchilla lanigera female carcasses, obtained from a private commercial farming unit in Cluj county, Romania were used for this study. Ten carcasses were used for the anatomical study, being injected into the vascular bed with a mixture of latex and acrylic dye, fixated into formaldehyde 5% and later dissected, while the other ten carcasses were injected at the level of the aortic arch with Visipaque 320 contrast substance and subjected to the angiographical procedure.The anatomical investigation was carried after an initial 5 day-fixation period, while the angiographic procedure was initiated using the TEMCO Grx-01 device and the Veterinary Digital Imaging System® as digital imaging processing software. This combined study shows the differential mode of emergence of the subclavian and carotid arteries in this species. The brachiocephalic trunk is the first large collateral branch arising from the initial part of the aortic cross while the left subclavian artery, in all studied cases, stems from this initial part of the aortic arch. The right subclavian artery arises from the terminal part of the brachiocephalic trunk, at the cranial border of the first rib. The continuation of the trunk is represented by right common carotid artery that follows the right jugular groove. The left common carotid artery emerges at the medial aspect of the first intercostal space as a collateral branch detached from the brachiocephalic trunk, in its initial sector. In respect to the collaterals emerging from the subclavian arteries, our study showed that in all studied cases, four branches arise in sequence- the internal thoracic, dorsal scapular, vertebral and superficial cervical arteries. The existence of the common trunks (internal thoracic, dorsal scapular arteries and superficial and deep cervical arteries (as described by other authors) was not confirmed on the investigated specimens. Discussion: The paper highlights some interesting facts referring to the specific morphology of the aortic arch in chinchilla, as literature data provides some divergent data. Some of the aspects noted are confirmed (the emergence of subclavian arteries) while some others are still subjects to discussion and further investigation (collateral branches of subclavian arteries). Our approach focuses also on the comparative aspects of the morphology of the branches emerging from the aortic arch. According to the available literature, the following species were used as comparison: leporids, Guinea pig, squirrel, yellow-necked mouse, Egyptian mouse, rat, armadillo, nutria, capybara, paca, fox and leopard.